Inhibition of transmembrane TNF-α shedding by a specific antibody protects against septic shock - Li, Chenxi; Gu, Haiyan; Yu, Mingxia; Yang, Peng; Zhang, Meng; Ba, Hongping; Yin, Yue; Wang, Jing; Yin, Bingjiao; Zhou, Xiaoxi; Li, Zhuoya (Cell death & disease, 2019)
Transmembrane TNF-α (tmTNF-α) and secretory TNF-α (sTNF-α) display opposite effects in septic shock. Reducing tmTNF-α shedding can offset the detrimental effects of sTNF-α and increase the beneficial effect of tmTNF-α. We previously developed a monoclonal antibody that is specific for tmTNF-α and does not cross-react with sTNF-α. In this study, we show that this antibody can specifically suppress tmTNF-α shedding by competing with a TNF-α converting enzyme that cleaves the tmTNF-α ectodomain to release sTNF-α. This tmTNF-α antibody significantly inhibited LPS-induced secretion of interleukin (IL)-1β, IL-6, interferon-β, and nitric oxide by monocytes/macrophages, and protected mice from septic shock induced by lipopolysaccharide (LPS) or cecal ligation and puncture, while reducing the bacterial load. The mechanism associated with the protective effect of this tmTNF-α antibody involved promotion of LPS-induced toll-like receptor 4 (TLR4) internalization and degradation by recruiting Triad3A to TLR4. Moreover, the tmTNF-α antibody inhibited LPS-induced activation of nuclear factor-κB and interferon regulatory factor 3 pathways by upregulating expression of A20 and monocyte chemotactic protein-induced protein 1. Similarly, treatment of macrophages with exogenous tmTNF-α suppressed LPS/TLR4 signaling and release of proinflammatory cytokines, indicating that increased levels of tmTNF-α promoted by the antibody contributed to its inhibitory effect. Thus, use of this tmTNF-α antibody for specific suppression of tmTNF-α shedding may be a promising strategy to treat septic shock.